Proclamation: Proclamation of Son Ahman, even Jesus Christ, to all peoples of the earth, even my holy will to warn all of my judgment upon all peoples - Jeffs, Warren (Fundamental Church of Jesus Christ of Latter-day Saints, 2011)
Thus saith Jesus Christ, even the ruler over all, who hath now sent you his word of judging and cleansing power, who now declareth judgment upon present Judge and law officials of present persecution against my Fundamentalist Church of Jesus Christ of Latter-day Saints; to know I am soon to judge all in government positions of unrighteous prosecution against my people, to show my will concerning present court persecuting power; which judge is now to be of my holy judging upon her and others who have mocked my holy religious and pure holy law of celestial plural marriage in open court: let all such proceedings cease now! - Introduction